A modified electrode for detection of biological material - Yusof, Nor Azah; Dutse, Sabo Wada; Ahmad, Haslina (2012)

(untitled)
The present invention relates to a modified electrode for detection of biological material. The modified electrode is used in electrochemical DNA biosensor for detecting Ganoderma boninense. The modified electrode comprises of a polymer, a nanoparticles and an oligonucleotide probe. Utilization of the modified electrode in detecting Ganoderma boninense enhances sensitivity of the detection.